1996
DOI: 10.1074/jbc.271.6.3097
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Radical Trapping Activity of a Novel Series of Cyclic Nitrone Spin Traps

Abstract: ␣-Phenyl-tert-butyl nitrone (PBN) is a nitrone spin trap, which has shown efficacy in animal models of oxidative stress, including stroke, aging, sepsis, and myocardial ischemia/reperfusion injury. We have prepared a series of novel cyclic variants of PBN and evaluated them for radical trapping activity in vitro. The cyclic nitrones were shown to trap ⅐ OH with MDL 101,002 being 20 -25 times more active than PBN as assessed using 2-deoxyribose and p-nitrosodimethylaniline as substrates, respectively. Trapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 28 publications
0
48
0
1
Order By: Relevance
“…9 Moreover, Asahi et al 39 reported that PBN effectively decreased tPA-induced hemorrhage in a rat embolic focal cerebral ischemia model. Hu et al 40 also showed that MDL 101,002, a conformationally constrained cyclic analogue of PBN, 41 reduced hemorrhage rate in rabbits after an embolism.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, Asahi et al 39 reported that PBN effectively decreased tPA-induced hemorrhage in a rat embolic focal cerebral ischemia model. Hu et al 40 also showed that MDL 101,002, a conformationally constrained cyclic analogue of PBN, 41 reduced hemorrhage rate in rabbits after an embolism.…”
Section: Discussionmentioning
confidence: 99%
“…, a spin-trapping reagent that reacts with many radicals, including superoxide, hydroxyl, lipid, and 1-hydroxyethyl radicals (33), produced a concentrationdependent decrease in COL1A2 mRNA levels in the E5 cells and completely prevented the increase by AA (Fig. 3C).…”
Section: N-t-butyl-␣-phenyl-nitrone (Pbn)mentioning
confidence: 95%
“…Ao mesmo tempo, vem sendo avaliado o valor terapêutico de citocinas com efeitos antiinflamató-rios (IL-10, IL-12 e interferon-gama (IFN-γ)). Também vêm sendo estudados: inibidores de fatores de transcrição, (11)(12)(13) inibidores da proteína ativada pela mitógene-quinase, (14) bloqueadores de adesão celular, inibidores de prostaglandinas, (15)(16)(17) antagonistas do fator ativador de plaquetas, (18,19) inibidores de fosfolipases, (20,21) antagonistas da bradicinina, (22)(23)(24) antioxidantes, (25,26) antagonistas de adenosina, (27)(28)(29) inibidores da NO-sintase, (30,31) antagonistas da endotelina, (32) inibidor da proteína básica do eosinófilo (33)(34)(35) e inibidores de enzimas inflamatórias. (36)(37)(38) .…”
Section: J Pneumol 29(6) -Nov-dez De 2003unclassified